A Multi-Story Expandable Systematic Hierarchical Construction Information Classification System for Implementing Information Processing in Highway Construction - Chung, Taewon; Bok, Jin Hoon; Ji, Hyon Wook (Applied sciences, 2023)
In the field of infrastructure construction, progress in digital transformation remains limited; this is particularly true in road construction, an infrastructure facility involving design, construction, and operation stages. Many construction subjects are involved at each stage of this cycle, generating substantial construction information. To drive the digital transformation of the construction industry, a construction information classification system is necessary for the development of a systematic construction information model. This study focuses on categorizing construction information into objects and activities, defining unit work by combining these two categories, and allowing for the flexible processing of construction information. A construction information classification system was developed, representing the evolving construction-related methodological information throughout the project’s lifecycle. Applying this multi-story expandable systematic hierarchical system to a highway project demonstrates the representation of key tasks in each construction phase, enabling the future stage-specific expansion of construction information for individual tasks. The proposed system could advance the digital transformation in infrastructure construction.